2020
DOI: 10.7717/peerj.9574
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota associated with symptom severity in schizophrenia

Abstract: Background The gut microbiome and microbiome-gut-brain (MGB) axis have been receiving increasing attention for their role in the regulation of mental behavior and possible biological basis of psychiatric disorders. With the advance of next-generation sequencing technology, characterization of the gut microbiota in schizophrenia (SZ) patients can provide rich clues for the diagnosis and prevention of SZ. Methods In this study, we compared the differences in the fecal microbiota between 82 SZ patients and 80 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 77 publications
9
63
1
1
Order By: Relevance
“…Furthermore, shifts in taxonomic abundance in SZs were consistent with previous studies. For instance, Roseburia (order Clostridiales) and Ruminococcus (order Lactobacillales) showed depletion in SZs, which was observed in multiple previous studies on psychiatric diseases 4,27,28 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, shifts in taxonomic abundance in SZs were consistent with previous studies. For instance, Roseburia (order Clostridiales) and Ruminococcus (order Lactobacillales) showed depletion in SZs, which was observed in multiple previous studies on psychiatric diseases 4,27,28 .…”
Section: Discussionsupporting
confidence: 65%
“…With the advent of sequencing technology, characterization of schizophrenia (SZ) with probing of the underlying gut microbiome can provide abundant clues for the diagnosis and prognosis of SZ 1 . Several published studies of the gut microbiome in SZ revealed that the species composition within the gut of individuals with SZ is different from that of normal control subjects (NCs), with varying bacterial taxa driving community separation in each study, and several of these studies have also focused on the relationship between different gut microbiota and clinical characteristics [2][3][4] . Converging evidence suggests that the gut microbiota communicates with the central nervous system bidirectionally through the microbiome-gut-brain (MGB) axis 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The DNA extraction method was consistent with our previously published report [4] . Sequencing of the V4 region of the16S rRNA gene was performed on the Illumina MiSeq platform.…”
Section: Fecal Sample Collection and Preprocessingsupporting
confidence: 70%
“…Finding effective and objective biomarkers to inform the diagnosis of schizophrenia (SZ) is of great importance yet remains challenging [1 2] . It is now broadly accepted that gut microbiota abundance, inflammation, immunological factors, and functional brain networks are altered in SZ [3][4][5][6] , however, most of these alterations are observed at the group level with great variability among individuals with the same phenotypic diagnosis Consequently, none so far has proven to have the ability to reliably aid in the differential diagnosis of SZ [1 7] . Therefore, it is important to analyze how gut microbiota abundance, inflammatory factors, immunological factors and functional brain networks behave at an individual level; for example, this information could be used to better understand the pathology and identify objective biomarkers for the clinical diagnosis of SZ [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in microbiota composition and microbial metabolites affect gut integrity and immune responses. Gut dysbiosis was observed in patients with schizophrenia, and the abundance of specific bacterial genera, Succinivibrio and Corynebacterium , were significantly associated with the symptom severity of schizophrenia [ 64 ]. The gut dysbiosis may affect the susceptibility to infection and inflammation, which can accelerate the development of schizophrenia and aggravate its symptom severity.…”
Section: Dietary Inflammation and Schizophreniamentioning
confidence: 99%